Detection of intracellular histological abnormalities using cardiac magnetic resonance T1 mapping in patients with Danon disease: a case series. Issue 5 (4th May 2021) - Suzuki, Hideaki; Morita, Yoshiaki; Saito, Ryoko; Tatebe, Shunsuke; Niihori, Tetsuya; Saiki, Yoshikatsu; Yasuda, Satoshi; Shimokawa, Hiroaki
Abstract: Background: Danon disease is an X-linked dominant disorder with defects in the lysosome-associated membrane protein 2 (LAMP2) gene and is characterized histologically by intracellular autophagic vacuoles in skeletal and cardiac muscles. Cardiac magnetic resonance (CMR) T1 mapping potentially allows to differentiate intracellular and extracellular cardiac abnormalities with a combination of native T1 value and extracellular volume (ECV) fraction. Case summary: We assessed CMR T1 mapping in two Danon disease patients (a 22-year-old man and his 48-year-old mother), who had a LAMP2 c.864G>A p. Val288Val mutation, and two blood relatives without Danon disease (his 47-year-old maternal aunt and 49-year-old father). The male patient underwent a left ventricular (LV) assist device implantation at 15 months after the image acquisition because he was inotrope dependent (INTERMACS profile 3) and had no noticeable psychological or musculoskeletal symptoms. His mother was in New York Heart Association Class II with mildly reduced LV ejection fraction (46%). The Danon group showed late gadolinium enhancement (LGE) in the anterior and posterolateral LV walls. In the interventricular wall, where evident LGE was not noted, the Danon group had high native T1 value, compared with the T1 value in the non-Danon group, and normal ECV fraction. Cardiac biopsy from the interventricular wall showed intracytoplasmic autophagic vacuoles, which are characteristics of Danon disease. Discussion: This characteristic pattern of high native T1 and normal ECV fraction in the areas without LGE, which may reflect the existence of intracytoplasmic autophagic vacuoles, may support the differential diagnosis of Danon disease from other cardiomyopathies.